The Effects of Tillage Systems and Cover Crops on Soil Quality and Soybean Yield - Qiliang Hunag; Yingting Gong; Peiran Li; Ratih Kemala Dewi; Masakazu Komatsuzaki (Agriculture)
Implementing management practices that minimize environmental impact while maintaining high crop yields is essential to achieve sustainable agricultural production. This study conducted a field trial within a soybean system to evaluate the responses of crop yield, residue decomposition, soil organic carbon (SOC) stock, and soil total nitrogen (STN) stock to varying tillage [moldboard tillage (MP) vs. no-tillage (NT)] and cover crop [hairy vetch (Vicia villosa Roth, HV) vs. rye (Secale cereal, RY)] management practices. The results showed no significant difference in soybean economic yield between MP and NT. However, NT demonstrated a higher SOC stock (0–30 cm), exceeding MP by 4.0% in 2020 and 8.2% in 2021. STN stock (0–30 cm) under NT also surpassed that of MP by 3.3% in 2020 and 3.6% in 2021. No significant differences were observed in soybean yield, SOC stock, and STN stock between HV and RY. Compared to NT, MP accelerated the decomposition of cover crop residues. Moreover, the decomposition of RY was more difficult than that of HV. These findings suggest that NT enhances soil carbon and nitrogen sequestration without compromising yield, positioning it as a sustainable practice for soybean systems, particularly when integrated with RY cover crops.